CANAL TRANSPORT INDEX AND ROOT CANAL CENTRALIZATION CAPACITY PROMOTED BY THE BIORACE, V-FILE, AND PROTAPER NEXT SYSTEMS: A CBCT STUDY - Oliveira, Helder Fernandes de; Ramos, Anna Clara Silva; Guardiano, Gabrielle Morais Carneiro Borges; Silva, Jordana Alves Garcia da; Amaral, Maria Teresa Andrade do; Camilo, Naiara Geovana; Boggian, Luciana Carvalho; Guedes, Orlando Aguirre (CIPEEX, 2025)
Objective: This study aims to analyze the transport index (TI) and centralization capacity (CC) of root canal preparation using different nickel-titanium instruments, based on images obtained by cone beam computed tomography (CBCT). Material and Methods: Forty-five mesiobuccal canals of lower molars were prototyped. Groups: The canals were randomly distributed into three groups (n=15) according to the rotary instrument used: G1: BioRace®, G2: V-File®, G3: Protaper Next®. CBCT images were obtained before and after canal preparation. Measurements were performed by two examiners using OsiriX® DICOM Viewer software. The analyses were performed 3 mm below the furcation of the teeth. The IT and CC were evaluated according to the methodology proposed by Gambill et al. (1996). The data obtained were analyzed using the Kruskal-Wallis test, with a significance level of 5%. Results: All instruments analyzed caused root canal transport and decentralization. BioRace® and V-File®: Tendency toward distal transport. Protaper Next®: Tendency toward mesial transport. No significant differences were found between the groups in terms of IT and CC (p<0.05). None of the instruments tested showed perfect centralization capacity (=1.0). Conclusion: None of the instruments, whether operated in continuous rotation or reciprocating kinematics, showed no transport or ideal centralization capacity of the root canal. All instruments evaluated caused some degree of transport and decentralization of the canals.